Pentahelix Collaboration in Enhancing Creative Economic Competitiveness Based on MDI Culture in West Sumatra Tourism Destinations - Irwan Irwan; Zusmelia Zusmelia; Ansofino Ansofino; Abather Rahi Saadoon; Kevin William Andri Siahaan (Universitas Teuku Umar, 2026)
This study aims to analyze the pentahelix actors in developing the competitiveness of the culture-based Creative Economy and MDI in West Sumatran tourist destinations. This study uses the pentahelix theory proposed by Etzkowitz & Leydesdorff (2000). This study uses a qualitative approach with a descriptive type and informant collection techniques using purposive sampling. The data collection method begins with document studies, non-participant observation, in-depth interviews, and focus group discussions (FGD). Data analysis in this study uses the Milles and Huberman method (1992) and uses Mactor software (Matrix of Alliances and Conflicts Tactics, Objectives and Recommendations). The results of this study indicate that the development of the creative economy in the competitiveness of the Creative Economy involves actors ranging from the media, government, society, academics, communities, and businesses, as well as banks. Actors involved in the Creative Economy are classified as very strong, namely the media, government, society, and academics. In addition, the pentahelix in developing the competitiveness of the culture-based creative economy in West Sumatran tourist destinations can create an advanced, innovative, and sustainable environment. Collaboration between parties in the pentahelix model can strengthen innovation, increase the competitiveness of tourist destinations, encourage the preservation of local culture, and create a creative economy ecosystem that is sustainable, inclusive, adaptive, and competitive at the national and global levels.